DIMINISHING INTER-LINKAGES OF THE SOUTH EAST EUROPEAN STOCK MARKETS - Naumoski, Aleksandar; Arsov, Sasho; Gaber, Stevan; Gaber naumoska, Vasilka (Academy of Economic Studies in Bucharest, Romania, 2017)
This paper investigates the level of relationship of the SEE stock markets in three analyzed periods: the pre-crisis, mid-crisis, and post-crisis period. We found that the relationships of the SEE markets with the benchmark developed markets, and among them, are not stable in the long-run. Using the VAR model, Granger cause causality, impulse response and variance decomposition, we came to the conclusion that while in the crisis period the SEE stock markets shows high interrelations among them and with the developed markets, the inter-linkages diminished after the crisis period. In the pre- and post-crisis period SEE markets have on average zero correlations, modest lead-lag interactions, small responses to other market shocks, and most of the variance is explained by their own shock. The opposite is true for the crisis period, when SEE markets have a significant adjusted effect, and each market responds to the impulses coming from most of the other markets. This suggests that in the period of instability and uncertainty SEE markets follow a common path, and in the calm periods with optimism and positive expectations the lead-lag relations of the SEE markets with the developed stock markets diminish.
Keywords: South East Europe, stock market integration, Granger cause causality, impulse response, variance decomposition